Exploring the Therapeutic Effects of Psychedelics Administered to Military Veterans in Naturalistic Retreat Settings - Megan Calnan; Grace Blest‐Hopley; Chris Busch; Milly Adams; Simon G. D. Ruffell; Theodore Piper; Leor Roseman; Hannes Kettner; Robin Carhart‐Harris (Brain and Behavior)
Abstract Background: Military veterans are at risk of various mental health conditions, with profound implications for post‐deployment quality of life. Current treatment options encounter high dropout rates and non‐responsiveness, and overlook the importance of community building in veterans’ holistic recovery. Preliminary research suggests psychedelics offer therapeutic benefits for depression and post‐traumatic stress disorder (PTSD) in veterans. Integrating psychedelic therapies with a communal retreat setting could provide a more holistic framework for improving veterans’ well‐being. Objectives: To evaluate the effects of psychedelic retreats on mental health and community reintegration in veterans. Methods: Fifty‐eight veterans attended psilocybin or ayahuasca retreats. Participants completed eight mental health questionnaires (e.g. PTSD Checklist, PCL‐5; Patient Health Questionnaire, PHQ‐9), and the Military to Civilian Questionnaire (M2C‐Q) up to 4 weeks both pre‐ and post‐retreat. Paired t‐tests analyzed changes in outcome responses between time points, and gender and substance‐specific analysis was conducted. Baseline scores were correlated with improvements in PCL‐5 and PHQ‐9 to investigate the relationship between initial symptom severity and percentage improvement following the retreat. Results: Significant improvements were found for all eight outcomes post‐retreat, with the greatest percentage improvements found for depression (PHQ‐9; 29.1%) and PTSD (PCL‐5; 26.1%). Veterans attending psilocybin retreats showed greater improvements in seven out of eight outcomes, whereas ayahuasca retreats demonstrated greater improvements in PCL‐5 scores for PTSD (ayahuasca: 26.4%; Psilocybin 24.8%). Male participants experienced greater improvements across all outcomes apart from the PCL‐5 for PTSD (Male: 24.1%; Female: 32.1%). Higher baseline scores on the PCL‐5 (PTSD) and PHQ‐9 (depression), indicating worse initial mental health, correlated with greater outcome improvements. Conclusions: This is the first study to investigate psychedelic retreats as a holistic therapy for veterans’ mental health alongside community reintegration. Psilocybin and ayahuasca retreats significantly improved veterans’ mental well‐being, quality of life, PTSD, anxiety, depression, sleep, concussion, and post‐deployment reintegration. Participants with more severe symptoms have the potential to benefit most from this intervention, with nuanced insight into improved outcomes based on gender and type of substance. Psychedelic retreats could provide a treatment framework to aid veterans’ recovery by addressing psychological well‐being, communal factors, and reintegration into civilian life.